Texture and Tractability: The Framework for Spatial Policy Analysis in the World Development Report 2009 - Deichmann, Uwe; Gill, Indermit; Goh, Chor-Ching (2012)
Development is accompanied by significant spatial transformations--changes in the distribution of people and economic activities. The World Development Report 2009 Reshaping Economic Geography draws lessons from history and academic research to develop a concise framework for understanding these dynamics. This framework makes rigorous spatial policy analysis tractable. But it has been criticize--mostly by geographer--for ignoring the "importance of place." This paper explains why it is necessary to draw out common patterns in the development experience of different countries even if this requires generalization and simplification. Recent applications at the urban, national, and regional level demonstrate how the framework accommodates contextual and place specific information to ensure the relevance of applied policy analysis.